The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1111/j.1751-1097.2012.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level Laser Therapy Ameliorates CCl4‐induced Liver Cirrhosis in Rats

Abstract: This study investigated the effects of low-level laser therapy (LLLT) in the liver function, structure and inflammation in a experimental model of carbon tetrachloride (CCl(4))-induced liver cirrhosis. Wistar rats were divided into Control, LLLT, CCl(4) and CCl(4) +LLLT groups. CCl(4) groups received CCl(4) (0.4 g kg(-1); i.p.), three times a week, for 12 weeks. A 830 nm LLLT was performed with a continuous wave, 35 mW, 2.5 J cm(-2) per point, applied to four points of the liver (right and left upper and lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Sassoli et al (2016) showed that PBM inhibited the TGF-β1/Smad3mediated fibroblast-myofibroblast transition. Additionally, PBM has been reported to reduce collagen deposition in rat tendons after trauma (Fillipin et al, 2005), carbon tetrachloride-induced liver cirrhosis (Oliveira-Junior et al, 2013), and renal interstitial fibrosis (Oliveira et al, 2012). According to our previous in vitro study, we showed that PBM could significantly reduce the pathological thickness in ANE-induced OSMF.…”
Section: Discussionmentioning
confidence: 67%
“…Sassoli et al (2016) showed that PBM inhibited the TGF-β1/Smad3mediated fibroblast-myofibroblast transition. Additionally, PBM has been reported to reduce collagen deposition in rat tendons after trauma (Fillipin et al, 2005), carbon tetrachloride-induced liver cirrhosis (Oliveira-Junior et al, 2013), and renal interstitial fibrosis (Oliveira et al, 2012). According to our previous in vitro study, we showed that PBM could significantly reduce the pathological thickness in ANE-induced OSMF.…”
Section: Discussionmentioning
confidence: 67%
“…CCl 4 has been used as the most common experimental model of chemically induced liver fibrosis (Ogeturk et al, ) and cirrhosis (Oliveira‐Junior et al, ) in rodents causing damages resemble those seen in human subjects (Mortezaee, Sabbaghziarani, et al, ). Metabolization of CCl 4 produces • CCl 3 that reacts with O 2 to form CCl 3 normalO2 (Shaker et al, ).…”
Section: The Role Of Oxidative Stress In Liver Fibrosis and Cirrhosismentioning
confidence: 99%
“…CCl 4 has been used as the most common experimental model of chemically induced liver fibrosis (Ogeturk et al, 2008) and cirrhosis (Oliveira-Junior et al, 2013) in rodents causing damages resemble those seen in human subjects .…”
Section: The Role Of Oxidative Stress In Liver Fibrosis and Cirrhosmentioning
confidence: 99%
“…Alkaline phosphatase (ALP) is another prominent enzyme from the group of catalytic enzymes, frequently distributed in brush border of intestinal mucosal cytosol, degrading phosphate esters and separating phosphoric acid molecules (Ghiasi Ghalehkandi et al, 2012). It is reported that low-level laser therapy significantly diminished carbon tetrachloride-increased ALP of rat liver (Oliveira-Junior et al, 2013).…”
Section: Introductionmentioning
confidence: 97%